The Influence of Education Level Through the Role of Fathers on Children's Independence and Discipline in Delang District, Lamandau Regency - Cintami, Pelisa Nagi; Rachman, Ali; Sari, Nina Permata (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to examine the direct and indirect effects of parents' educational level through the father's role on the development of independence and discipline in early childhood in Delang District, Lamandau Regency. The regression analysis results indicate that both educational level and the father’s role significantly affect children's independence (β = 0.484; β = 0.147) and discipline (β = 0.184; β = 0.137), with p-values less than 0.05. The Sobel test also confirms significant indirect effects of parental education on independence (Z = 2.85) and discipline (Z = 2.108) through the father’s involvement. These findings emphasize that higher parental education tends to encourage more active father involvement, which in turn plays a key role in shaping children's character, particularly in terms of independence and discipline. The study recommends promoting the educational role of fathers and supporting family-based education as essential foundations for positive early childhood development.